Banff Fibrosis Study: Multicenter Visual Assessment and Computerized Analysis of Interstitial Fibrosis in Kidney Biopsies. Issue 4 (20th February 2014) - Farris, A. B.; Chan, S.; Climenhaga, J.; Adam, B.; Bellamy, C. O. C.; Serón, D.; Colvin, R. B.; Reeve, J.; Mengel, M.
<x xml:space="preserve">Abstract</x> Increasing interstitial fibrosis (IF) in native and kidney transplant biopsies is associated with functional decline and serves as a clinical trial end point. A Banff 2009 Conference survey revealed a range in IF assessment practices. Observers from multiple centers were asked to assess 30 renal biopsies with a range of IF and quantitate IF using two approaches on trichrome, Periodic acid‐Schiff (PAS) and computer‐assisted quantification of collagen III immunohistochemistry (C‐IHC) slides, as well as assessing percent of cortical tubular atrophy% (TA%) and Banff total cortical inflammation score (ti‐score). C‐IHC using whole slide scans was performed. C‐IHC assessment showed a higher correlation with organ function (r = −0.48) than did visual assessments (r = −0.32–−0.42); computerized and visual C‐IHC assessment also correlated (r = 0.64–0.66). Visual assessment of trichrome and C‐IHC showed better correlations with organ function and C‐IHC, than PAS, TA% and ti‐score. However, visual assessment of IF, independent of approach, was variable among observers, and differences in correlations with organ function were not statistically significant among C‐IHC image analysis and visual assessment methods. C‐IHC image analysis correlated among three centers (r > 0.90, p < 0.0001, between all centers). Given the difficulty of visual IF assessment standardization, C‐IHC image could potentially accomplish standardized IF assessment in multicenter settings.